Boosting H2 Production from a BiVO4 Photoelectrochemical Biomass Fuel Cell by the Construction of a Bridge for Charge and Energy Transfer. Issue 27 (2nd June 2022) - Wang, Zhaoqi; Guo, Yuhao; Liu, Mu; Liu, Xiaolei; Zhang, Haipeng; Jiang, Weiyi; Wang, Peng; Zheng, Zhaoke; Liu, Yuanyuan; Cheng, Hefeng; Dai, Ying; Wang, Zeyan; et al.
Abstract: Utilizing a photoelectrochemical (PEC) fuel cell to replace difficult water oxidation with facile oxidation of organic wastes is regarded as an effective method to improve the H2 production efficiency. However, in most reported PEC fuel cells, their PEC activities are still low and the energy in organic fuels cannot be effectively utilized. Here, a unique BiVO4 PEC fuel cell is successfully developed by utilizing the low‐cost biomass, tartaric acid, as an organic fuel. Thanks to the strong complexation between BiVO4 and tartaric acid, a bridge for the charge and energy transfer is successfully constructed, which not only improves the photoelectric conversion efficiency of BiVO4, but also effectively converts the chemical energy of biomass into H2 . Remarkably, under AM1.5G illumination, the optimal nanoporous BiVO4 photoanode exhibits a high current density of 13.54 mA cm −2 at 1.23 V vs reversible hydrogen electrode (RHE) for H2 production, which is higher than that of previously reported PEC water splitting systems or PEC fuel cell systems. This work opens a new path for solving the low PEC H2 production efficiency and provides a new idea for improving the performances and energy conversion efficiency in traditional PEC fuel cells. Abstract : A unique BiVO4 photoelectrochemical fuel cell is successfully developed by utilizing the low‐cost tartaric acid biomass as an organic fuel. The strong complexation between BiVO4 and tartaric acid provides a bridge for charge and energy transfer. The optimal BiVO4 photoanode exhibits a remarkable current density of 13.54 mA cm −2 at 1.23 V versus reversible hydrogen electrode under AM1.5G.